The Influence of Organizational Climate and Career Development on Employee Job Satisfaction in The Sumedang Resort Police Drug Unit - Maulana Maulana; Harries Madiistriyatno; Widya Nengsih (Dinasti International Journal of Management Science, 2026)
The aim of the research is to describe and analyze the influence of organizational climate on employee job satisfaction, the influence of career development on employee job satisfaction and The influence of organizational climate and career development simultaneously on employee job satisfaction in the Sumedang Police Narcotics Investigation Unit. The calculated t value for variable X1 (organizational climate) is 5.068, while the t table value for N = 45 is 2.014. So 5.068 > 2.014, it can be concluded that partially the organizational climate variable influences employee job satisfaction, the calculated t value for variable X2 (career development) is 4.904, while the t table value for N = 45 is 2.014. So 4.904 > 2.014, it can be concluded that partially the career development variable influences employee job satisfaction. The calculated F value is 54.879, which is greater than the F table of 2.81 with a significance level of 0.000 because 0.000 < 0.05, so it can be said that the organizational climate variable (X1) and the career development variable (X2) together have a positive effect on the employee job satisfaction variable (Y). The R Square value is 0.723. This shows that 72.3% of the organizational climate and career development simultaneously (together) have a positive effect on employee productivity, while the remaining 27.7% is influenced by other factors not examined in this study.